Establishing A Global Algorithm For Water Quality Mapping From Multi-Dates Images. - Lim, H.S.; Mat Jafri, M.Z.; Abdullah, K.; Bakar, M.N.A. (2003)
Water quality assessment of ocean and inland waters using satellite data has been carried out since the first r satellite Landsat-MSS has been operational (Thiemann and Kaufmann, 2000).